1988
DOI: 10.1055/s-2006-962424
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Digoxin Content inDigitalis lanatain Controlled Conditions and Natural Environment

Abstract: In two different populations of Digitalis lanata (P7 interbreeding, L 3-2A first generation inbreeding),the influence of environmental and genetic factors relative to digoxin production have been studied in controlled conditions and in the field. In controlled conditions (artificial light of 300 ixflnf2r'), digoxin content first increased rapidly and then became stable. At the end of the increasing phase, plants had reached the morphologic stage "dense rosette" and digoxin content was maximal. Under weaker nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…These results are quite similar to those reported by Brugidou et al (1988) in D. lanata plants grown in controlled conditions and natural environment. These authors found that the variability in cardenolide production of D. lanata, expressed as digoxin contents, was related with the seasonal variations of light intensity, photoperiod and thermoperiod.…”
Section: Seasonal Variations Of Cardenolidessupporting
confidence: 91%
See 2 more Smart Citations
“…These results are quite similar to those reported by Brugidou et al (1988) in D. lanata plants grown in controlled conditions and natural environment. These authors found that the variability in cardenolide production of D. lanata, expressed as digoxin contents, was related with the seasonal variations of light intensity, photoperiod and thermoperiod.…”
Section: Seasonal Variations Of Cardenolidessupporting
confidence: 91%
“…3). In this respect, Brugidou et al (1988) pointed out photoperiodism and a more accented daily thermoperiodism of late summer and early autumn as the main factors involved in the decrease of digoxin rate in D. lanata plants. Nevertheless, the fact that cardenolides have been found in different sink organs and move around phloem sap (Vogel and Luckner, 1981;Rothe et al, 1999) suggests that catabolism and translocation may also provoke a decrease in the leaf cardenolide contents during the autumn.…”
Section: Seasonal Variations Of Cardenolidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A grande variação individual nas concentrações de cardenolídeos no cultivar experimental já era esperada, uma vez que estas plantas não foram submetidas a nenhum processo de seleção, sendo constituídas por indivíduos com uma ampla base genética. Avaliações anteriores em populações nativas e cultivares de D. lanata, de diferentes origens, indicaram uma alta variabilidade intra-específica nos teores dos cardenolídeos quantificados 5,6,7,12,15 que este material resultou da clonagem de plantas selecionadas, sendo constituído por uma base genética estreita.…”
Section: Resultsunclassified
“…In the case of Digitalis plants, previous studies have reported that cardenolide biosynthesis is basically dependent on morphological differentiation [22] and genotype [23], although numerous environmental factors may determine, in a greater or lesser degree, plant productivity. Thus, it is known the influence that mineral nutrients [24,25], CO2 and water stress [26], and light conditions [27] exert on cardenolide accumulation. Moreover, in our previous papers, we showed that H2O2 pre-treatment [15] and elimination of Ca, Mg or both from the medium [28] resulted in an increase in cardenolides, enzymatic and non-enzymatic antioxidants in callus cultures of Digitalis davisiana Heywood, Digitalis lamarckii Ivanina, Digitalis trojana Ivanina and Digitalis cariensis Boiss.…”
Section: Discussionmentioning
confidence: 99%